A model for pumping optimization in edge-pumped disk amplifiers. (December 2022) - Palla, D.; Labate, L.; Baffigi, F.; Cellamare, G.; Gizzi, L.A.
Abstract: A model for the calculation of the pump energy coupling to a disk amplifier is presented. The disk is considered to be pumped on its edge by diode bars. A composite geometry, namely a disk with a doped (pump absorbing) inner region surrounded by an undoped region is considered. The model allows the overall pump energy coupling as well as the absorption 3D map to be obtained for different geometric diode bars arrangements on an N-sided polygon. A set of fundamental conditions for the maximization of the total energy coupled to the active region is laid out first. Using the model, we then show that once these conditions are fulfilled, the precise diode bars arrangement and focusing can be tuned to get the desired energy absorption spatial distribution, while preserving the highest overall energy coupling to the doped region. The most interesting case of a cylindrically symmetric, radially uniform absorption profile is discussed, providing some general hints on achieving such a condition. Highlights: Model of pump energy absorption in edge-pumped amplifiers. Criteria for maximizing pump energy coupling. Optimizing pump energy distribution pattern in edge-pumped amplifiers.